Adapting and validating the satisfaction, alertness, timing, efficiency, and duration-breast cancer (SATED-BC) scale for measuring sleep health in Spanish women treated for breast cancer - Ángela González-Santos; Mario Lozano-Lozano; Irene Cantarero-Villanueva; Paula Postigo-Martín; Lydia Martín-Martín; Rocío Gil-Gutiérrez; Roberto Muelas-Lobato; Maria Lopez-Garzon (Women's Health)
Background: After breast cancer (BC), women may face other severe symptoms such as sleep problems. The use of simple, fast, and reliable scales is necessary in the clinic to improve patient benefits, and sleep is an important aspect to be addressed. Objective: This study was conducted to adapt and validate the Spanish version of the satisfaction, alertness, timing, efficiency, and duration (SATED) scale for measuring sleep health in women who have completed treatment for BC in Spain (SATED-BC). Design: Cross-sectional study. Methods: The adaptation process involved adding a sixth item to the SATED-BC scale: “the impact of symptoms experienced after completing breast cancer treatment on sleep” item was not considered for scoring. The SATED-BC score ranged from 0 (poorest sleep health) to 10 (best sleep health). A validation analysis was performed using the Pittsburgh Sleep Quality Index, the Consensus Sleep Diary, and actigraphy, and the results were compared with those obtained using the SATED-BC scale. Results: The SATED-BC scale was reliable in terms of its internal consistency (Cronbach’s α = 0.70; McDonald’s ω = 0.72), showed high intrasubject reliability ( r  = 0.90), and was shown to be valid for use in women who have completed treatment for breast cancer. Conclusion: The SATED-BC scale is a reliable and valid tool for comprehensively evaluating sleep health in women who have completed treatment for breast cancer.